Computer Vision-Based Intelligent Traffic Surveillance: Multi-Vehicle Tracking and Detection - Husein, Amir Mahmud; Noflianhar Lubis, Kevi; Salim Sidabutar, Daniel; Yuanda, Yansan; Kevry; Waren, Ashwini (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The application of vehicle detection in real-time traffic surveillance systems is one of the challenging research fields with different objectives. One of the problems is the detection of many vehicles simultaneously in a video sequence sourced from CCTV cameras. In many works, the focus is only on detecting vehicle classes such as motorcycles, buses, trucks, and cars or special vehicles such as ambulances and others. In this research, we propose to apply 13 classes of vehicle types and implement YOLOv4 in the traffic surveillance task. More specifically, all classes are labeled, and then the YOLOv4 model is trained on 800 images and tested on 23 videos from three intersections in Medan City, namely Juanda Katamso Intersection, Gatot Subroto Intersection, and Uniland Intersection. Based on the test results, YOLOv4 proves successful in detecting many vehicles in frame-by-frame sequence with various types of vehicles. All vehicle detection data will be stored in the file.